2020
DOI: 10.3390/jcm10010029
|View full text |Cite
|
Sign up to set email alerts
|

Why Venous Leg Ulcers Have Difficulty Healing: Overview on Pathophysiology, Clinical Consequences, and Treatment

Abstract: Venous leg ulcers (VLUs) are one of the most common ulcers of the lower extremity. VLU affects many individuals worldwide, could pose a significant socioeconomic burden to the healthcare system, and has major psychological and physical impacts on the affected individual. VLU often occurs in association with post-thrombotic syndrome, advanced chronic venous disease, varicose veins, and venous hypertension. Several demographic, genetic, and environmental factors could trigger chronic venous disease with venous d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
128
0
23

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 144 publications
(152 citation statements)
references
References 182 publications
1
128
0
23
Order By: Relevance
“…Venous ulcers (VUs) are caused by chronic venous insufficiency and have a preponderance for the lower extremity. 53,54 The United Kingdom leads research on VU and studies by the National Health Service (NHS) identified that 1 in 500 UK residents have VU costing an estimated £400-600 million in health care costs. 55 In the United States, an estimated 500,000-600,000 people have venous leg ulcers resulting in a nearly $1 billion burden on health care.…”
Section: Venous Ulcersmentioning
confidence: 99%
“…Venous ulcers (VUs) are caused by chronic venous insufficiency and have a preponderance for the lower extremity. 53,54 The United Kingdom leads research on VU and studies by the National Health Service (NHS) identified that 1 in 500 UK residents have VU costing an estimated £400-600 million in health care costs. 55 In the United States, an estimated 500,000-600,000 people have venous leg ulcers resulting in a nearly $1 billion burden on health care.…”
Section: Venous Ulcersmentioning
confidence: 99%
“…These structural changes may be eccentric (increased remodeled arterial lumen) to accommodate reduced luminal space due to atherogenic lesions or post-intraluminal restenosis, to maintain adequate blood flow [ 14 ]. However, these changes may be concentric (reduction in remodeled arterial lumen) due to prolonged wall tension and vasoconstriction as in hypertension [ 14 , 16 , 17 ].…”
Section: Vascular Remodelingmentioning
confidence: 99%
“…Altered shear stress could lead to injury to the glycocalyx, endothelial dysfunction and progression of CVD. The glycocalyx structure is markedly altered and is associated with increased inflammation in CVD and VVs [75] . The glycocalyx is composed of glycoproteins with acidic oligosaccharides and terminal sialic acid, proteoglycans (heparan sulfate proteoglycan, syndecans and glypican core proteins), and glycosaminoglycan side chains that are sulfated (chondroitin sulfate, dermatan sulfate, heparan sulfate, keratan sulfate, and heparin), and nonsulfated (hyaluronic acid).…”
Section: Inflammation and Mmps In Cvdmentioning
confidence: 99%
“…SDX has also shown some benefits in diabetic microangiopathy and nephropathy, advanced CVI and VLU [182,185,187] . Experimental studies have also shown beneficial actions of SDX including reduction of oxidative stress [188] , modulation of growth factors, decreased MMP expression, reduced inflammation, anti-angiogenic effects [189] , and protection of endothelial cells [14,75,[190][191][192][193][194][195] .…”
Section: Sdx In Venous Leg Ulcermentioning
confidence: 99%